The Effectiveness Of The Application Of The Field Trip Method In Learning Arabic Language To Improve Writing Skills For Grade 8 At Madrasah Tsanawiyah Darul Faizin Mojowarno Jombang - Abidin, Hasan (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2022)
This study explains about